The Relationship Between Personality and the Perception of the Ambiguous Necker Cube Stimuli - Pallaris, Cypriana (My University, 2023)
Perception is the process by which an individual interprets their surrounding environment. The current study seeks to investigates the relationship between personality and the perception of the ambiguous Necker cube stimuli. More specifically the present study seeks to examine the relationship between the big-five personality traits and the perception of Necker cube stimuli as well as how these relationships may be moderated by cognitive flexibility and cognitive empathy. The present study also, examined the involvement of bottom-up and top-down processes in the before mentioned relationships. In this study there was a total of 160 participants sampled globally (i.e. the United Kingdom, the European Union, Australia, the United Arab Emmerits, Malaysia, India, and the United States of America). The present study consisted of three task conditions: a passive condition, hold condition, and a switch condition. There were 20 trials (16 experimental and 4 control) included in each of these three task conditions, and in each trial, stimuli were presented in pairs. In each task condition participants were instructed on how they should attempt to direct their perception of the second stimuli presented. In the passive condition participants were instructed to passively perceive the stimuli, in the hold condition participants were instructed to hold their initial perception of the first stimuli, and in the switch condition participants were asked to reverse their initial perceptual interpretation of the first stimuli presented. The dimensions of personality that were examined in the current study include the big-five personality traits (i.e., openness, conscientiousness, extroversion, neuroticism, and agreeableness), cognitive flexibility, and cognitive empathy. In this study effects on reversal rates were only observed in the switch and hold task conditions which are the conditions requiring top-down processes. From this it can be surmised personality has an influence on reversal rates at the level of top-down processes. Each of the big-five personality traits were found to have an effect on reversal rates when moderated by either cognitive flexibility or cognitive empathy.
Keywords: Personality, Perception, Big-Five Personality Traits, Necker cube, Cognitive flexibility, Cognitive empathy, Bottom-up processes, and Top-down processes